Increase in Ca2+-Activated cAMP/PKA Signaling Prevents Hydroxychloroquine-Induced Bradycardia of the Cardiac Pacemaker - Segal, Sofia; Arbel-Ganon, Limor; Mazgaoker, Savyon; Davoodi, Moran; Yaniv, Yael (Frontiers in Physiology, 2022)
Bradycardia or tachycardia are known side effects of drugs that limit their clinical use. The heart pacemaker function which control the heart rate under normal conditions is determined by coupled clock system. Thus, interfering with specific clock mechanism will affect other clock mechanisms through changes in interconnected signaling and can lead to rhythm disturbance. However, upregulation of a different clock components can compensate for this change. We focus here on hydroxychloroquine (HCQ), which has been shown effective in treating COVID-19 patients, however its bradycardic side effect limits its clinical use. We aim to decipher the mechanisms underlying the effect of HCQ on pacemaker automaticity, to identify a potential drug that will eliminate the bradycardia. We used isolated rabbit sinoatrial node (SAN) cells, human-induced pluripotent stem cell–derived cardiomyocytes (hiPSC-CMs) and mouse SAN cells residing in SAN tissue. Further, we employed SAN cell computational model to suggest mechanistic insights of the effect of HCQ on pacemaker function. HCQ increased mean spontaneous beat interval and variability in all three models in parallel to slower intracellular kinetics. The computational model suggested that HCQ affects the pacemaker (funny) current (If), L-type Ca2+ current (ICa,L), transient outward potassium (Ito) and due to changes in Ca2+ kinetics, the sodium-calcium exchanger current (INCX). Co-application of 3’-isobutylmethylxanthine (IBMX) and HCQ prevented the increase in beat interval and variability in all 3 experimental models. The HCQ-induced increase in rabbit and mice SAN cell and hiPSC-CM spontaneous beat interval, can be prevented by a phosphodiester inhibitor that restores automaticity due to slower intracellular Ca2+ kinetics.